Medium optimization for high cell mass and exopolysaccharides production using paenibacillus polymyxa - Daud, Nur Sazwani (2022)
Paenibacillus polymyxa ATCC 842 is one of the beneficial microbes that shows high potential to promote plant growth and enhance soil health by producing a variety of beneficial secondary metabolites specifically exopolysaccharides (EPS). This study aimed to optimize medium composition for enhancing the production of cell mass and EPS by P. polymyxa ATCC 842 using statistical methods for agriculture application. At first, the one-factor-at-a-time (OFAT) method was used to screen the cultivation medium of P. polymyxa ATCC 842 which was reported previously for high cell mass and EPS production. Then, different ranges concentration of the main components of selected media were investigated such as sucrose, yeast, phosphate and MgSO4. Based on the OFAT results, three factors were selected as the most influence factors: sucrose, yeast extract, and K2HPO4 for the medium optimization through statistical approaches by using response surface methodology (RSM). The Box Behnken design (BBD) was used to evaluate the effects of variables on the cell mass and EPS production. The optimal medium composition by RSM composed of sucrose, 30 g L-1; yeast extract, 30 g L-1; K2HPO4, 5.72 g L-1; NH2NO4, 5 g L-1; KH2PO4, 1.9 g L-1 and MgSO4, 0.5 g L-1 . Under the optimized medium, the cell mass of P. polymyxaATCC 842 about 20.36 g L-1, which was 7.51-fold higher than the unoptimized medium (2.71 gL-1). Meanwhile, the EPS was increased 16.46 g L-1, about 6.71-foldhigher than the unoptimized medium (2.45 g L-1) after 36 hours of cultivation at pH7.0, 30 °C, and agitation speed at 150 rpm. The model was found to be significant and subsequently validated through the growth kinetics studies in the unoptimized andoptimized medium by RSM. The result revealed that the optimized medium was ableto support better growth of P. polymyxa ATCC 842 with a specific growth rate of 1.397h-1 and EPS productivity about 0.68 g L-1h-1. Furthermore, to understand the physio-chemical of EPS from P. polymyxa ATCC 842, a series of biochemistry characteristics were investigated. High-Performance Liquid Chromatography (HPLC) analysis revealed that EPS of P. polymyxa ATCC 842 is composed of monomer fructose and glucose. Meanwhile, Fourier-transforms infrared spectroscopy analysis showed the presence of hydroxyl, carboxyl groups, and glycosidic linkages which showed the composition of the polysaccharide bound by a-(1?6). The scanning electron micrographs analysis showed EPS appears as a homogenous spherical with irregular porosity for high water holding capacity of the soil. The EPS structure could result ina higher water absorption/ retention capacity, which is an attractive feature for a sticky agent for soil aggregation. P. polymyxa ATCC 842 with the spent mushroom substrate(SMS) as soil amendment gives the best result in neutralizing the pH and forming soil aggregate including phosphate and potassium improvements. In conclusion, the optimized production medium shows significant effects on enhancing the growth of P.polymyxa ATCC 842 and maximum secretion of EPS and indirectly, promotes the application of P. polymxya ATCC 842 as the beneficial candidate for sustainable agricultural practices.